Pengaruh Social Media Promotion, Menu Variations, dan Price Bundling Terhadap Purchasing Decision - Fajariana, Dewi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Home industry is an internal part of MSMEs in Indonesia that is related in terms of business scale, economic contribution, and role in local empowerment. Home industry is one of the easiest alternatives in opening up business opportunities to earn income. The purpose of this research is to test and analyze the influence of social media promotion, menu variations, and price bundling on purchasing decisions. The research approach used is quantitative with the type of explanatory research. The source of research data is primary data with data collection techniques using questionnaires. The research population was 1173 respondents based on purchase data from January to December 2024. The sampling technique used the Slovin formula, so that the number of research samples was 92 respondents. The data analysis method used instrument testing, classical assumption testing, and multiple linear regression analysis. The results of the study showed that simultaneously and partially social media promotion, menu variations, and price bundling had a significant effect on purchasing decisions for home industry products.